A Correlation Between The Level Of Knowledge And Attitudes Of Adolescents With The Prevention Behavior Of Human Immunodeficiency Virus (HIV) At Sman 07 Of Bengkulu City In 2024 - Klana, Fredy Putra; Wulandari, Wulandari; Pebriani , Emi (Multidisciplinary Journals, 2025)
The estimated number of people with HIV in Indonesia in 2022 was 540,568 people with 24,276 new infections and 27,374 deaths. This study aims to determine the correlation between the level of knowledge and attitudes of adolescents with the behavior of preventing transmission of Human Immunodeficiency Virus (HIV) at SMAN 07 of Bengkulu City in 2024. The research method used was descriptive quantitative research with a cross sectional approach. Sampling technique using Proportionate Stratified Random Sampling technique with the number of samples in this study 90 people representing all students at SMAN 07 of Bengkulu City. The results of univariate test analysis Almost most respondents (41.1%) with good knowledge, most respondents (55.6%) with positive attitudes, most respondents (61.1%) with good HIV transmission prevention behavior. The results of bivariate analysis showed the level of knowledge (0.000) and attitude (0.000) of adolescents with the behavior of preventing transmission of Human Immunodeficiency Virus (HIV). There is a correlation between the level of knowledge and attitude of adolescents with the behavior of preventing transmission of Human Immunodeficiency Virus (HIV) at SMAN 07 of Bengkulu City in 2024. Researchers suggest that for SMAN 07 of Bengkulu City the results of this study can be the basis for the implementation of guidance, coaching, and counseling activity programs on the behavior of preventing transmission of Human Immunodeficiency Virus (HIV).